The evolution of economic governance in EMU - Noord, Paul van den.; Dohring, Bjorn; Langedijk, Sven.; Martins, Joao Nogueira; Pench, Lucio R.; Temprano - Arroyo, Heliodoro; Thiel, Michael; European Commission : Directorate-General for Economic and Financial Affairs (Brussels- Belgium : European Comission : Directorate-General for Economic and Financial Affairs, 2008)
This paper examines the benefits of co-ordination in EMU in a stylised manner and how these benefits have shaped the co-ordination framework in EMU. It then discusses in detail the co-ordination experience in four areas that are particularly important for the functioning of EMU: (i) fiscal policy co-ordination under the Stability and Growth Pact (SGP); (ii) the co-ordination of structural policies under the Lisbon Strategy for Growth and Jobs; (iii) the representation and co-ordination of euro-area positions in international financial fora; and (iv) the co-ordination of macroeconomic statistics. The thrust of the findings is that EMU's system of economic governance has, overall, proven fit for purpose. The current policy assignment to the institutions and instruments that govern the conduct of economic policy in EMU is sound, even though further progress is necessary in several areas, particularly as regards external representation.
Economic Papers